Principle of separation of powers in the old Oyo empire as a template for the contemporary political structure in Nigeria (2021)
The well- structured political administrative set-up of the old Oyo Empire allowed relative peace to reign in various communities and traditional rulers were not left out as they were charged with the responsibility of ensuring that there was peaceful co-existence among people in those communities. Therefore, for there to be peace in the old Oyo Empire, the Alaafin and his Council of Chiefs known as the Oyo-Mesi developed a structure built on the principle of separation of powers to address various conflict related matters. This was borne out of the fact that for development to be achieved in any community, people must live in peace no matter what. In order to achieve this, separation of power was put in place to avoid usurpation of duty and overlap of functions. The peaceful co-existence experienced in the old Oyo Empire was made possible due to this deeply rooted principle. Existing studies on the roles played by Alaafin and his chiefs in the old Oyo Empire have mainly focused on the social, economic and religious perspectives with little attention paid to how Alaafin in council made use of the principle of separation of powers to resolve conflicts, and how such strategies can be adopted as a template in the contemporary political structure in Nigeria today.